A stable and reliable data dissemination scheme based on intelligent forwarding in VANETs. (5th December 2018) - Chahal, Manisha; Harit, Sandeep
Summary: Vehicular ad hoc networks (VANETs) have gained incredible attention because of their applications in safety, commercial uses, and traffic management. However, the dynamic topology changes caused by the high speed of vehicles raise many challenges for the effective data dissemination in vehicular applications. In this paper, with the objective to solve the problem of frequent disconnection during data delivery, we propose a novel, intelligent forwarding–based stable and reliable data dissemination scheme. First, link stability is described mathematically, by which vehicle chooses the next forwarding node. Then, a greedy algorithm is presented to transmit the data from source to destination. A separate recovery algorithm is also designed to resolve the intermediate link breakage problem. The performance of the proposed method is analyzed by performing extensive network and traffic simulations with respect to various indexes such as latency, packet delivery ratio (PDR), and throughput. Compared with the state‐of‐the‐art protocols, the proposed method under varying density improves the average PDR and throughput by 31.55% and 25.30%, respectively. Abstract : We propose a novel intelligent forwarding–based stable data dissemination scheme. Link stability is described mathematically with lemmas and their proof, by which vehicle chooses the next forwarding node. A greedy algorithm and a separate recovery algorithm during intermediate link breakage are designed. The experimental results show that our proposed method outperforms the state‐of‐the‐art protocols.